Perception, Impact And Determinants Of Climate Change Adaptation Among Vegetable Growers Of Dhading District Of Nepal (SAARC Journal of Agriculture, 2020)
Climate change is one of the most challenging problems for the agricultural development. The purpose of this study is to analyze perception of climate change, its impacts and determinants among vegetable growers and to identify major adaptation strategies used by them. The study was based on survey of 75 vegetable growers; 34 from Benighat Rorang rural municipality and 41 from Siddhalek rural municipality of Dhading district of Nepal. Data were collected using face to face interview. The study provided empirical evidence of decreased in intensity, duration and frequency of rainfall and increase in annual temperature, drought duration and frost severity. Incidence of disease and pest, decline in soil fertility, scarcity of water and severe frost/hailstones were major problems. The 45.33% vegetable growers were compelled to change planting and 54.67% of them to change harvesting due to climate change effect. The adaptation practices such as mulching (24%), green/plastic house (29.3%), drip irrigation (8%), IPM (12.5%), change in crop variety (31.3%) and cropping pattern were found common practices adopted by farmers. The probability of adapting climate change mitigating factors was 70.26% higher for those who had received training in vegetable cultivation. Use of new climate smart agricultural technologies and providing training about vegetable cultivation were found suitable strategies to mitigate the negative impacts of climate change.SAARC J. Agri., 17(2): 239-251 (2019)